2013
DOI: 10.1021/ma4007736
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Dependence on the Disintegration of Spin-Assisted Weak Polyelectrolyte Multilayer Films

Abstract: We present the effect of molecular weight (MW) of polyelectrolytes (PEs) on the disintegration behavior of weak PE multilayer films consisting of linear poly(ethylene imine) (LPEI) and poly(methacrylic acid) (PMAA). The multilayer films prepared by the spin-assisted layer-by-layer deposition have well-ordered internal structures and also show the linear thickness growth behavior regardless of MWs of PMAA. The well-defined weak PE multilayer films were subject to disintegration into bulk solution when the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 50 publications
6
47
0
Order By: Relevance
“…For both film types, the pH and enzymatic stability was improved with increasing PVCL length and β-sheet content, indicating enhanced hydrophobic and hydrogen-bonded interactions between PVCL and silk. 32,46,57,58 In our case, the increase in multilayer thickness alongside molecular weight in dipped films correlates well with the increase in PVCL radius of gyration in solution, R g . Our approach gives a unique opportunity to tune thickness, morphology, structure, and biodegradability rate of silk films and capsules by varying silk secondary structure and PVCL length.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…For both film types, the pH and enzymatic stability was improved with increasing PVCL length and β-sheet content, indicating enhanced hydrophobic and hydrogen-bonded interactions between PVCL and silk. 32,46,57,58 In our case, the increase in multilayer thickness alongside molecular weight in dipped films correlates well with the increase in PVCL radius of gyration in solution, R g . Our approach gives a unique opportunity to tune thickness, morphology, structure, and biodegradability rate of silk films and capsules by varying silk secondary structure and PVCL length.…”
supporting
confidence: 65%
“…32,46,57,58 In our case, the increase in multilayer thickness alongside molecular weight in dipped films correlates well with the increase in PVCL radius of gyration in solution, R g . Film thickness, surface morphology, wettability, and pH-stability are strongly controlled by deposition conditions and PVCL molecular weight.…”
supporting
confidence: 65%
“…Film swelling, ion exchange, mobility of film components, 89,90 and potential interactions with proteins and cells could result in gradual destabilization of the films; 91 and the rate of dissolution has been shown to be influenced by polyelectrolyte MW. 92 Studies have shown that PLL/HA films formulated with 40-60 kDa PLL and 64 kDa HA dissolved in~16 days in 1× PBS, 93 while PLL/HA multilayers built with 30 kDa PLL but higher MW HA (400 kDa) were stable in sodium chloride solution for several months and for at least 2 weeks in contact with cells and culture media. 94 For PLL 30 and PLL 90 films, the number of effective uses correlated with film stability in media ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[2, 1113] The overall properties of the film can be controlled simply by adjusting processing parameters: nature of polyelectrolytes, functional groups, molecular weight, charge density, concentration of the adsorption species, adsorption and rising time, pH, ionic strength, and humidity. [1419]…”
Section: Introductionmentioning
confidence: 99%